Analisis SWOT Potensi Industri Asuransi Syari’ah Di Indoneasia : Studi Pendekatan Vivo dan Literatur Review - Rohmadi; Doni Yusuf Bagaskara (Universitas Muhammadiyah Metro, 2024)
This research aims to determine a SWOT analysis regarding the potential of the ShariaInsurance Industry in Indonesia using the NVivo approach. This research uses qualitativemethodology with the NVivo approach and literature review.